Evaluasi Mutu Fisik, Total Bakteri, Dan Sensori Minuman Sari Tempe Dengan Penambahan Bunga Kecombrang - Indah Tri Minarni; Wikanastri Hersoelistyorini; Agus Suyanto (Jurnal Pangan dan Gizi, 2021)
Tempe juice drink is a functional drink made from the main ingredient of tempe, which has a good nutritional composition for the body, preservation of tempeh juice drinks currently uses chemicals using benzoic acid, the use of benzoic acid can have an impact on health.Kecombrang flowers contain bioactive components such as alkaloids, polyphenols, flavonoids, essential oils, phenolics, and triterpenoids which can function as antibacterial.The addition of kecombrang flowers is intended to prolong or preserve the tempeh juice.The purpose of this study was to determine the total bacteria test, viscosity, and sensory quality of tempeh juice drink with variations in the addition of kecombrang flowers and storage time.This research is an experimental type using factorial Completely Randomized Design (CRD) with the dependent variable including the total test for bacteria, viscosity, and sensory quality, while the independent variable includes the addition of kecombrang flowers and storage time. The research stages included making kecombrang flower powder and making tempeh juice.The process of making tempeh juice drinks through cutting, milling, boiling, filtering, packaging, and storage. The treatment of adding kecombrang flowers (0%, 0.5%, 1%, 1.5%) and storage time (0 hours, 4 hours, 8 hours, 12 hours). The resulting product is carried out in the test stages for total bacteria, viscosity, and sensory quality (color, aroma, taste, consistency).The results showed that the interaction between the addition of kecombrang flowers and storage time had a significant effect on total bacteria, viscosity, aroma, taste, consistency, and had no significant effect on color.The best treatment was obtained in the addition of 1.5% kecombrang flower treatment and 8 hours of storage, with total bacteria (2.8x104 colonies / gram), viscosity (0.145 Cp), sensory (2.83).